Including Social Housing Residents in the Energy Transition: A Mixed-Method Case Study on Residents' Beliefs, Attitudes, and Motivation Toward Sustainable Energy Use in a Zero-Energy Building Renovation in the Netherlands - Bal, Michèlle; Stok, F. Marijn; Van Hemel, Carolien; De Wit, John B. F. (Frontiers in Sustainable Cities, 2021)
Reducing household energy use in social housing buildings can substantially contribute to mitigating global climate change. While municipalities and social housing corporations are willing to invest in sustainable renovations and innovations, social housing residents’ inclusion in the sustainable energy transition lags behind. This pilot study explored social housing residents’ attitudes toward sustainability and sustainable renovation of their apartment building, as well as (factors underlying) their motivation toward two specific sustainable behaviors. Semi-structured interviews, containing both open- and close-ended questions, were conducted with twenty residents of one social housing building that was due for renovations. Results showed that respondents were concerned about climate change, including environmental justice beliefs, typically already engaged in various sustainable behaviors, and were motivated to add sustainable behaviors to their repertoire after the renovation. Yet, perceived social norms were not always supportive of behaving sustainably and respondents sometimes failed to recognize the sustainable value of these behaviors. Furthermore, while respondents were more positive than negative about the sustainable renovation, they nevertheless listed many concerns and problems regarding the renovation process, including procedural justice concerns. This pilot study provided important insights into the barriers and facilitators of the sustainable energy transition among social housing residents, who are at risk of lagging behind in the sustainable urban energy transition. Findings underline the importance of including residents in the sustainable renovation process through engagement, communication, and co-creation.